Marriage of the rain goddess : a South African myth - Margaret Olivia Wolfson; Clifford Alexander Parms (Barefoot Beginners, 1998)
A retelling of a Zulu myth about the joining of heaven and earth when Mbaba Mwana Waresa, the rain goddess, chooses a mortal for her husband